Perancangan Aplikasi Pengacakan Pemenang Undian Berhadiah Menggunakan Metode Blum-Blum Shub Berbasis Android - Citono Harahap; Garuda Ginting; Taronisokhi Zebua (STMIK Budi Darma, 2020)
Lottery or commonly known as a lottery is one way to raise funds used for humanitarian projects and social activities or a way to determine the winner randomly. So, the lottery does a random gift-giving process and the lottery is synonymous with the lottery. The design of a lottery winner randomization application is one of the more modern ways and can attract many lottery participants to enter the lottery by reducing the cost of printing and distributing lottery tickets. One of them is the blum blub shub method, which is a method that functions to generate random numbers mathematically with the resulting output is a series of binary numbers. the numbers that are made as winners. The designed application only simulates the process of inputting lottery numbers and the randomization process to get the winning numbers